Echinococcosis at urology. Pelvic parasitic cyst. Case report - A. I. Tkachenko; S. G. Chetverikov; A. M. Chaika; V. V. Lysachenko (Kazimierz Wielki University, 2019)
Introduction. Echinococcosis is a serious chronic parasitic disease. Early diagnostics and patients` treatment with echinococcal lesions is an up-to-date problem. Objective. The aim of the article is to present the clinical case of diagnostics and treatment of the patient with urological complications caused by parasitic echinococcal pelvic cyst. Clinical case. The article highlights the features of diagnostics and treatment of urological complications of pelvic echinococcal lesions. The patient was operated in volume: "Laparotomy. Resection of parasitic cyst of small pelvic cavity. Echinococcectomy of the liver, abdominal cavity, retroperitoneal space." The peculiarities of operation was highlighted. The postoperative period lasted without complications. Conclusions. The demonstrated clinical case points out the necessity of the dispanserisation, early diagnostics and special helminth treatment of the patients living in the endemic regions. It allows to prevent the appearance of the echonococcosis advanced cases that lead to the reoperations and frequent patients` disability.